Postoperative Return to Play and the Role of Imaging - Brumbaugh, Aaron D.; Casagranda, Bethany U. (Seminars in Musculoskeletal Radiology, 2024)
Return to play (RTP) following surgery is a complex subject at the interface of social and internal pressures experienced by the athlete, psychological readiness, and intrinsic healing of the surgically repaired structures. Although functional testing, time from surgery, clinical examination, and scoring metrics can help clarify an athlete's readiness to return to sport, imaging can allow for a more direct assessment of the structures in question. Because imaging is often included in the diagnostic work-up of pain following surgery, the radiologist must be familiar with the expected postsurgical imaging appearance, as well as the associated complications. We briefly review such findings following anterior cruciate ligament reconstruction, Achilles tendon repair, syndesmotic fixation, and ulnar collateral ligament reconstruction in the context of the athlete, highlighting issues related to RTP.
Keywords: return to play; anterior cruciate ligament reconstruction; ulnar collateral ligament reconstruction; syndesmotic fixation; Achilles repair